2020
DOI: 10.1016/j.ejvs.2020.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Choice – International Variations and Sex Disparities in the Treatment of Peripheral Arterial Occlusive Disease: A Report from VASCUNET and the International Consortium of Vascular Registries

Abstract: Objective: The aim of this study was to determine sex specific differences in the invasive treatment of symptomatic peripheral arterial occlusive disease (PAOD) between member states participating in the VASCUNET and International Consortium of Vascular Registries. Methods: Data on open surgical revascularisation and peripheral vascular intervention (PVI) of symptomatic PAOD from 2010 to 2017 were collected from population based administrative and registry data from 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 34 publications
2
29
3
Order By: Relevance
“…Open and/or hybrid surgery cases are performed in a dedicated vascular theatre by vascular surgeons; however, data is lacking on the number of purely hybrid procedures. The mean proportion of patients treated by endovascular procedures vs. open surgery between 2010 and 2017 was 68% (67-70, 95% confidence interval) in Malta [13]. This proportion was similar to that present in a number of European countries which participated in an international registry-based observation study [13].…”
Section: Paod-related Vascular Registrysupporting
confidence: 57%
See 1 more Smart Citation
“…Open and/or hybrid surgery cases are performed in a dedicated vascular theatre by vascular surgeons; however, data is lacking on the number of purely hybrid procedures. The mean proportion of patients treated by endovascular procedures vs. open surgery between 2010 and 2017 was 68% (67-70, 95% confidence interval) in Malta [13]. This proportion was similar to that present in a number of European countries which participated in an international registry-based observation study [13].…”
Section: Paod-related Vascular Registrysupporting
confidence: 57%
“…The mean proportion of patients treated by endovascular procedures vs. open surgery between 2010 and 2017 was 68% (67-70, 95% confidence interval) in Malta [13]. This proportion was similar to that present in a number of European countries which participated in an international registry-based observation study [13]. Although Mater Dei hospital lacks a dedicated vascular hybrid theatre, plans to build one are ongoing and approval for this has already been obtained.…”
Section: Paod-related Vascular Registrysupporting
confidence: 54%
“…While 28 RCTs in the first meta-analysis enrolled 33% females [1] and 8 RCT in the second meta-analysis enrolled 29% females [2], the current study was undertaken within a dataset more representative of everyday clinical practice that included 54% females. The latter seems more representative for the disease under study since a recent comparison of more than 1 million hospitalizations in 11 countries revealed that females represent approximately 40% (between 23% in Portugal and 46% in Sweden) of the cohort treated with both open-surgical and endovascular revascularizations [11]. A recent systematic review of 69 PAOD trials in the USA showed that females were appropriately represented in less than 16% of these trials, while the percentage of females in the underlying PAOD population was 53.1% [34].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there is clear evidence of striking differences between the sexes concerning various aspects of PAOD treatments (including prevention, best medical treatment, and revascularization procedures) and outcomes [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This lag was supported by a VASCUNET report showing that the proportion of endovas-cular peripheral vascular operations, compared to open procedures, was the lowest in Russia (24%), while the proportion in WECs ranged from 57% to 88%. Additionally, it was shown that the proportion of patients presenting with intermittent claudication vs. chronic limb-threatening ischemia was the highest in Russia (69%), while the average proportion in WECs was 37% [44].…”
Section: Processesmentioning
confidence: 99%